Percy Jackson and the Sea of Monster - Riordan, Rick (London: Puffin books, 2018)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke
Keywords: English , Fiction